1976
DOI: 10.1111/j.0954-6820.1976.tb06754.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Representative Male Survivors of Myocardial Infarction Compared with Representative Population Samples

Abstract: A series of 299 men, aged 27-67, who had survived their first myocardial infarction (MI), have been compared with representative population samples with respect to tobacco consumption, alcoholic intemperance, physical activity during work and leisure time, Occurrence of hypertension, and cholesterol and triglyceride levels in serum. The infarction patients comprised 90% of all surviving, diagnosed cases of primary MI in men aged 67 years or below during 1%70 in Goteborg, Sweden. The comparison between infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, the present study was started because of previous findings in a prospective population study in which several risk factors were checked for. In that study we found a signifcant, and independent, contribution to the risk for ischaemic heart disease manifestations (myocardial infarction and sudden coronary death) from alcoholic intemperance (4), and later these findings were corroborated in a casecontrol study (6). Recently it has been found that young Acta Med Scand 213 infarct patients aged below 40 were registered for intemperance twice as often as controls (16).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the present study was started because of previous findings in a prospective population study in which several risk factors were checked for. In that study we found a signifcant, and independent, contribution to the risk for ischaemic heart disease manifestations (myocardial infarction and sudden coronary death) from alcoholic intemperance (4), and later these findings were corroborated in a casecontrol study (6). Recently it has been found that young Acta Med Scand 213 infarct patients aged below 40 were registered for intemperance twice as often as controls (16).…”
Section: Discussionmentioning
confidence: 70%
“…Several recent Anglo-Saxon studies have shown lower incidence of coronary heart disease in people with moderate alcohol consumption than in teetotalers and heavy consumers (1, 2, 3). Other studies have reported increased morbidity and mortality in cardiovascular diseases among people with high alcohol consumption or abuse (4)(5)(6)(7)(8). Elmfeldt et al (6) found a significantly increased number of men registered for alcoholic intemperance among those who died outside hospital from cardiovascular disease aged around 50.…”
mentioning
confidence: 99%